Vascular endothelial growth factor and risk of malignant brain tumor: A genetic correlation and two-sample Mendelian randomization study - Zhang, Qiaoyun; Wu, Guangheng; Zhang, Xiaoyu; Zhang, Jie; Jiang, Mengyang; Zhang, Yiqiang; Ding, Lixiang; Wang, Youxin (Frontiers in Oncology, 2023)
Objective The relationship between vascular endothelial growth factor (VEGF) and the risk of malignant brain tumors has always been a concern in the medical field. However, the causal inferences from published observational studies on this issue may be affected by confounders, coinheritability and reverse causality. We aimed to investigate the causal relationship between VEGF and different types of malignant brain tumors. Methods Using publicly available summary data from genome-wide association studies (GWAS) of VEGF (n=16,112) and different types of malignant brain tumors (n=174,097-174,646), we adopted a standard two-sample bidirectional Mendelian randomization (MR) to estimate potential causal associations of circulating VEGF levels and the risk of malignant brain tumors. Inverse variance weighted (IVW) was used as the primary analysis method to estimate causality. MR-Egger regression, weighted median (WM), penalty weighted median (PWM), MR robust adjusted profile score (MR.RAPS) and causal analysis using summary effect estimates (CAUSE) methods were used in sensitivity analyses to verify the robustness of the findings. Meanwhile, we applied the MR pleiotropy residual sum and outlier (MR-PRESSO) test and PhenoScanner tool to identify and remove potential horizontal pleiotropic single nucleotide polymorphisms (SNPs). Additionally, linkage disequilibrium score regression (LDSC) analysis was conducted to assess the coinheritability of exposure and outcome. Results A total of 6 (VEGF), 12 (malignant brain tumor), 13 (brain glioblastoma) and 12 (malignant neoplasm of meninges) SNPs were identified as valid instrumental variables. No evidence supported a causal relationship between circulating VEGF levels and the risk of malignant brain tumors (forwards: odds ratio (OR) = 1.277, 95% confidence interval (CI), 0.812~2.009; reversed: β = 0.005, 95% CI, -0.029~0.038), brain glioblastoma (forwards: OR (95% CI) = 1.278(0.463~3.528); reversed: β = 0.010, 95% CI, -0.002~0.022) and malignant neoplasm of meninges (forwards: OR (95% CI) = 0.831(0.486~1.421); reversed: β = 0.010, 95% CI, -0.030~0.050) using the main IVW method. Outliers and pleiotropy bias were not detected by sensitivity analyses and pleiotropy-robust methods in any estimates. LDSC failed to identify genetic correlations between VEGF and different types of malignant brain tumors. Conclusions Our findings reported no coinheritability and failed to provide evidence for causal associations between VEGF and the risk of different types of malignant brain tumors. However, certain subtypes of VEGF for which genetic predictors have not been identified may play a role and need to be further investigated.